Geography of real estate prices in Mexico City: Variability and heterogeneity of values recorded in online advertisements - Antonine Ribardière (Unité Mixte de Recherche 8504 Géographie-cités, 2017)
The purpose of this article is to explore an original database, built from on-line real estate listings during the summer of 2014. The database allows us to capture the housing market visible by this way, at the scale of the metropolitan area and at two compliance levels: the level of the census units on the one hand, the level of the types of settlement on the other. Primarily, we remind the context of the housing market in the early 2000s in Mexico City, in particular the different forms of housing production. Secondly, we examine the spatial variability of the prices, reflecting the classical patterns of the social division of urban space in Mexico City, and highlighting the internal subdivisions in each types of settlement. All in all, the very wide price brackets demonstrate the substantial pressures on the residential space in the Mexican capital. Keywords: Mexico City, property values, housing market, population, social divisions of space